Heat stress and recovery effects on the physiology and biochemistry of Castanea sativa Mill. - Dorado, Javier F.; Pinto, Glória; Monteiro, Pedro; Chaves, Natividad; Alías, Juan Carlos; Rodrigo, Sara; Camisón, Álvaro; Solla, Alejandro (Frontiers in Forests and Global Change, 2023)
Chestnut forests are undergoing increasing heat stress due to the current global warming, but little is known about the physiology and biochemistry responses of Castanea sativa Mill. to heat or whether differences exist between populations. Six-month-old seedlings from three climatically contrasting populations of C. sativa (from the north, centre, and south of Spain) were subjected to control and heat stress conditions for 7 days. The effects of heat stress on seedlings and their recovery (10 days after heat stress) were described by assessment of visible symptoms, growth, mortality, and leaf gas exchange of plants, quantification of compounds involved in the primary and secondary metabolism, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging. In response to stress, plant biomass decreased, and plant biochemistry altered depending on the tissue and the population. Major alterations in the primary metabolism of stressed plants occurred in leaves, characterized by increased levels of soluble sugars, nitrogen, and proline, and depletion of starch. Increased levels of soluble sugars and starch depletion occurred mostly in seedlings from the southern population, while proline increase occurred only in the northern population. Secondary metabolism of seedlings experienced the highest variation below ground, and roots of heat-stressed plants increased the content of phenolic compounds. LC-MS analysis permitted identification and quantification of six compounds induced by heat, five of which were detected in the roots. Differential biochemistry responses to heat stress were observed among populations. At recovery, most of the altered parameters had returned to control conditions, suggesting high resilience to heat stress in this Mediterranean tree species. This is the first study to address the effects of heat stress on the physiology and biochemistry of C. sativa and their interpopulation variability. Most parameters were significantly influenced by the interaction of population and heat treatment, indicating that genetic differentiation controlled the phenotypic differences of C. sativa in response to heat stress. Extensive genetic variation in plasticity in physiological and biochemical parameters in response to heat stress reveals an opportunity for chestnut for global warming-mediated selection.